Analisis Model Integrasi Kartu Keanggotaan Perpustakaan Universitas Riau dengan Kartu Sakti Perpustakaan Nasional Republik Indonesia - Ajir; Yasin Setiawan; Asmawati (Jurnal Gema Pustakawan, 2023)
SAKTI (One Indonesian Card) is an Indonesian government program that creates one account for all government services, including libraries. National Library has socialized one card for all libraries in Indonesia, which technically can be done through membership integration between library institutions, including the UNRI Library. However, a big problem arises when two different systems can be made part of the SAKTI card. This research aims to find and recommend a model for integrating UNRI Library members with SAKTI National Library membership, both of which use different standards. The method used is SDLC (System Development Life Cycle), which includes Analysis, Design, Development, Implementation, Testing and Evolution, with the research object Slims-integrated UNRI Library and National Library Membership System. The devices used to realize the model include software (Inlislite), network (internet network), member ID (NIK / Population Identification Number), synchronization (Inlislite SAKTI), and scheduler (Cron). The process used in model development includes: Processing the "member" table in integrated slims, adjusting the database structure, synchronization testing, real synchronization, and installing the scheduler. The research results show that the model that can be used consists of an integrated Slims automation system that is adapted to National Library SSO standards and assisted by synchronization software from National Library. The model that was built succeeded in automatically integrating the collection of 7,560 people from 37,668 members of the UNRI Library.